2023
DOI: 10.1021/acs.inorgchem.3c01545
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Lattice Planes of NiCo-LDH Ultrathin Sheets for Boosting Methanol/Ethanol Oxidation Performance

Abstract: Alcohol oxidation reactions are known to be significant in the advancement of sustainable, renewable energy sources. Searching for catalytic materials with powerful, reliable, and economic performance is of great importance. Due to their excellent intrinsic performance, outstanding stability, and inexpensiveness, ultrathin layered double hydroxides (LDHs) are considered to be competitive electrocatalysts. However, the electrocatalytic property of ultrathin LDHs is still confined by the predominant exposure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The OER is an unwanted side reaction in NiO x alkaline batteries, and it has long been found that Fe impurities enhance such a process, [66–69] with this attracting significant attention to the effects of Fe‐doping in NiO x electrodes for OER electrocatalysis in alkaline media. Many studies have indeed shown that Fe‐doped nickel oxides are promising electrocatalysts for the OER [70–74] .…”
Section: Layered Cobalt‐based Oxidesmentioning
confidence: 99%
“…The OER is an unwanted side reaction in NiO x alkaline batteries, and it has long been found that Fe impurities enhance such a process, [66–69] with this attracting significant attention to the effects of Fe‐doping in NiO x electrodes for OER electrocatalysis in alkaline media. Many studies have indeed shown that Fe‐doped nickel oxides are promising electrocatalysts for the OER [70–74] .…”
Section: Layered Cobalt‐based Oxidesmentioning
confidence: 99%
“…The majority of the reported NiCo-based electrocatalysts demonstrated complete methanol oxidation to convert methanol into CO 2 , but it is required to selectively convert methanol into a valuable formate product. 37,42,43 Based on the above considerations, we present structural and electronic modification approaches to overcome the selectivity and durability issues of the active sites during MOR. The porous nanostructures of 3D bimetallic Ni−Co with surface oxygen vacancies were generated on 3D nickel foam (O v -NiCo@NF) by an ultrafast and environment-friendly electro-deposition method without using any soft/hard template as a proficient composite that efficiently catalyzes both MOR and HER at the anode and cathode, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Most reported NiCo-based electrocatalysts were synthesized using challenging synthesis protocols at high temperatures and pressures, which required more time and money, so synthesis protocols should be ultrafast and environmentally friendly. , Soft/hard templates have been utilized to create porosity in porous nanostructured materials, but removing these templates required harsh conditions and extra effort. , The durability of electrocatalysts is an important factor in MOR activity, and most of the reported electrocatalysts had very low durability because the CO intermediate generated during methanol oxidation blocked the active sites. , As a result, there is an urgent need to develop electrocatalysts with high durability for MOR. The majority of the reported NiCo-based electrocatalysts demonstrated complete methanol oxidation to convert methanol into CO 2 , but it is required to selectively convert methanol into a valuable formate product. ,, …”
Section: Introductionmentioning
confidence: 99%